DESIGN OF A CLEAN WATER DISTRIBUTION NETWORK SYSTEM IN JUBA CITY, CENTRAL EQUATORIA STATE, SOUTH SUDAN - Garang Geu Deng Garang Garang; Moch. Zenurianto (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
Juba City, situated about 457 meters above sea level, features flat terrain near the River Nile and is surrounded by gentle hills. The city has an area of 52 Km2 with a population of 500,000 people. This thesis aims to project the population for the year 2033, design a clean water distribution network system. Key data used includes historical population figures, topographic information, facility layouts, water source flow rates, and cost estimates. The analysis involved the use of Microsoft Excel, Google Earth Pro, QGIS, Civil 3D, EPACAD, and AutoCAD, with the main distribution system design carried out using EPANET 2.2 software. The projected population by 2033 is 669,735 people, with an estimated clean water demand of 2.288 m³/s. Water loss was calculated at 0.343 m³/s. The proposed network is designed as a dead-end system, consisting of 3,783 nodes and a total pipeline length of 218,862 meters. The distribution system uses HDPE PN 16 pipes, specifically 6-inch pipes totaling 127,823.8 meters and 4-inch pipes totaling 91,038.3 meters. The total budget for the project is estimated at Rp. 140.3 billion with 7 months implementation period.